Phylogeny of Courtship and Male-Male Combat Behavior in Snakes - Senter, Phil (Public Library of Science, 2014)
BACKGROUND: Behaviors involved in courtship and male-male combat have been recorded in a taxonomically broad sample (76 species in five families) of snakes in the clade Boidae + Colubroidea, but before now no one has attempted to find phylogenetic patterns in such behaviors. Here, we present a study of phylogenetic patterns in such behaviors in snakes. METHODOLOGY/PRINCIPAL FINDINGS: From the literature on courtship and male-male combat in snakes we chose 33 behaviors to analyze. We plotted the 33 behaviors onto a phylogenetic tree to determine whether phylogenetic patterns were discernible. We found that phylogenetic patterns are discernible for some behaviors but not for others. For behaviors with discernible phylogenetic patterns, we used the fossil record to determine minimum ages for the addition of each behavior to the courtship and combat behavioral repertoire of each snake clade. CONCLUSIONS/SIGNIFICANCE: The phylogenetic patterns of behavior reveal that male-male combat in the Late Cretaceous common ancestors of Boidae and Colubridae involved combatants raising the head and neck and attempting to topple each other. Poking with spurs was added in Boidae. In Lampropeltini the toppling behavior was replaced by coiling without neck-raising, and body-bridging was added. Phylogenetic patterns reveal that courtship ancestrally involved rubbing with spurs in Boidae. In Colubroidea, courtship ancestrally involved chin-rubbing and head- or body-jerking. Various colubroid clades subsequently added other behaviors, e.g. moving undulations in Natricinae and Lampropeltini, coital neck biting in the Eurasian ratsnake clade, and tail quivering in Pantherophis. The appearance of each group in the fossil record provides a minimum age of the addition of each behavior to combat and courtship repertoires. Although many gaps in the story of the evolution of courtship and combat in snakes remain, this study is an important first step in the reconstruction of the evolution of these behaviors in snakes.